(untitled) (Research, Society and Development, 2021)
Objectives: To assess methodological differences between studies that analyzed the association between hypertensive syndromes of pregnancy and prematurity. Methods: This is an integrative literature review, carried out between September 2020 and January 2021. The search for articles was performed in the PubMed, Virtual Health Library, Embase, Web of Science and Scopus databases based on combination of the following descriptors: (“Pregnancy Induced Hypertension” OR “High Risk Pregnancy”) AND (“Prematurity” OR “Prematury Birth” OR “Premature Neonate” OR “Neonate Prematurity”). Results and Discussion: 582 articles were found, only nine were selected. The main methodological disparities observed were related to the classification of hypertensive syndromes of pregnancy and prematurity, age of participants and control of confounders. Of the total number of selected studies, five informed the different guidelines used for the classification of syndromes and six used a cutoff point below 37 weeks for prematurity. Most articles found an association between the different categories of hypertensive syndromes and prematurity. Conclusion: Despite the methodological differences observed between the studies, an association was found between hypertensive syndromes of pregnancy and prematurity. For comparative purposes, it is recommended that further studies use current international guidelines to define hypertensive syndromes and prematurity. In addition, it is important to emphasize the importance of adequate prenatal care in order to monitor and treat women with hypertensive syndromes in order to reduce complications resulting from this clinical condition, especially prematurity.